Edukasi efektivitas vitamin E pada warga Asem Jajar Surabaya: Edukasi efektivitas vitamin E pada warga Asem Jajar Surabaya - Emilia Devi Dwi Rianti; Ayly Soekanto Ayly Soekanto; Putu Oky Ari Tania Putu Oky Ari Tania (JCS, 2023)
Vitamin E is very important for skin health, because as a bioactive compound, it is very important in the pathogenesis of the skin, although it shows a decrease in vitamin E levels in patients who experience skin diseases. The method used in community service is providing education about the effectiveness of vitamin E on skin health, and administering vitamin E. There were 35 residents who attended the education. The teaching aids used are in the form of a Flichat describing knowledge about improving skin health and Vitamin E. Evaluation of community service activities, namely; Women in the RT environment. 03 Asem Jajar Surabaya received counseling on maintaining healthy skin, understanding and knowing the benefits of vitamins. The results and discussion in using a device to measure moisture or skin oil levels with the MR213 LCD Monitor, which is an LCD Digital Skin Detector device, are 31.43% aged 41-55 years and 2.9% aged 81-90 years. The skin moisture of the residents showed no influence based on age, because some residents aged 60 years had skin humidity of 60%, and those aged 55 years had humidity of 45%. The high vitamin E content functions to help care for the skin. Providing vitamin E to residents aims to ensure that residents consume vitamin E for healthy skin. The conclusion of the education on the effectiveness of vitamin E for residents of RT.03 Asem Jajar Surabaya is very useful, because residents lack knowledge about skin care and skin benefits.